2005
DOI: 10.1038/sj.bjc.6602809
|View full text |Cite
|
Sign up to set email alerts
|

Diet, vegetarian food and prostate carcinoma among men in Taiwan

Abstract: In a case -control study in a veterans hospital in Taiwan, we compared 237 histology-confirmed prostate carcinoma cases with 481 controls, frequency matched by age, for their consumption of vegetarian food, namely soybean products, rice, wheat protein and other vegetables. The multivariable logistic regression analysis showed a significant association with such food (odds ratio 07, 3.30). Stratified analysis also showed that the consumption of fish/shellfish had an adverse association for men with higher BMI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 27 publications
1
48
1
3
Order By: Relevance
“…A despeito dos questionamentos dos efeitos adversos do consumo de soja transgênica, deve-se considerar também que essa leguminosa, na sua forma convencional, tem sido amplamente apontada como agente de prevenção ao câncer (CHEN et al, 2005;GUTIERREZ et al, 2005;INAGAKI et al, 2005). Importantes efeitos biológicos têm sido atribuídos às isoflavonas, como atividade antioxidante (ESAKI et al, 1999;NAIM et al, 1976), antiaterogênica (HUI et al, 2001), hipocolesterolêmica (LUI et al, 2003), propriedades estrogênicas (PARK et al, 2001), além do potencial anticarcinogênico (COWARD et al, 1993) e inibição da atividade enzimática (ESTEVES; MONTEIRO, 2001).…”
Section: Introductionunclassified
“…A despeito dos questionamentos dos efeitos adversos do consumo de soja transgênica, deve-se considerar também que essa leguminosa, na sua forma convencional, tem sido amplamente apontada como agente de prevenção ao câncer (CHEN et al, 2005;GUTIERREZ et al, 2005;INAGAKI et al, 2005). Importantes efeitos biológicos têm sido atribuídos às isoflavonas, como atividade antioxidante (ESAKI et al, 1999;NAIM et al, 1976), antiaterogênica (HUI et al, 2001), hipocolesterolêmica (LUI et al, 2003), propriedades estrogênicas (PARK et al, 2001), além do potencial anticarcinogênico (COWARD et al, 1993) e inibição da atividade enzimática (ESTEVES; MONTEIRO, 2001).…”
Section: Introductionunclassified
“…It is believed that a reduction in fat consumption would result in reduction in prostate cancer incidence. 47,48 Figure 1 Citrate metabolism and fatty acid pathway. Fats are broken down to fatty acids and glycerol.…”
Section: Diet Fat and Prostate Cancermentioning
confidence: 99%
“…Based on data from 11 case-cohort studies (La Vecchia et al, 1991;Ewings et al, 1996;Gronberg et al, 1996;Jain et al, 1999;Sung et al, 1999;Bosetti et al, 2004;Sonoda et al, 2004;Chen et al, 2005;Ukoli et al, 2009;Tyagi et al, 2010;Deneo-Pellegrini et al, 2012), we found no association between high intake of eggs and risk of prostate cancer (OR 1.09, 95% CI 0.89-1.31) (Figure 2). There was a significant heterogeneity between studies (p = 0.022, I 2 = 52.2%).…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Of all studies reviewed, three cohort studies presented RR estimates for fatal prostate cancer (Snowdon et al, 1984;Hsing et al, 1990;Richman et al, 2011). Seven studies were conducted in US/Canada (Snowdon et al, 1984;Mills et al, 1989;Severson et al, 1989;Hsing et al, 1990;Le Marchand et al, 1994;Jain et al, 1999;Richman et al, 2011), six in Europe (La Vecchia et al, 1991;Ewings et al, 1996;Gronberg et al, 1996;Schuurman et al, 1999;Bosetti et al, 2004;Allen et al, 2008), five in Asia (Sung et al, 1999;Allen et al, 2004;Sonoda et al, 2004;Chen et al, 2005;Tyagi et al, 2010), one in Negeria (Ukoli et al, 2009) and one in Uruguay (Deneo-Pellegrini et al, 2012). Overall, this meta-analysis included 5791 cases of prostate cancer, and most studies suggested a non-significant relationship between eggs consumption and prostate cancer.…”
Section: Figure 1 Flowchart Of Study Searchmentioning
confidence: 99%
See 1 more Smart Citation